2009
DOI: 10.1093/nar/gkp427
|View full text |Cite
|
Sign up to set email alerts
|

ToppGene Suite for gene list enrichment analysis and candidate gene prioritization

Abstract: ToppGene Suite (http://toppgene.cchmc.org; this web site is free and open to all users and does not require a login to access) is a one-stop portal for (i) gene list functional enrichment, (ii) candidate gene prioritization using either functional annotations or network analysis and (iii) identification and prioritization of novel disease candidate genes in the interactome. Functional annotation-based disease candidate gene prioritization uses a fuzzy-based similarity measure to compute the similarity between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
2,442
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 2,660 publications
(2,453 citation statements)
references
References 41 publications
8
2,442
0
3
Order By: Relevance
“…Proteomics data were assessed to identify enriched gene ontologies using the ToppFun application within the ToppGene suite [16]. Where proteomic-based gene annotation did not match HUGO gene symbols, ToppFun performed automatic re-annotation.…”
Section: Methodsmentioning
confidence: 99%
“…Proteomics data were assessed to identify enriched gene ontologies using the ToppFun application within the ToppGene suite [16]. Where proteomic-based gene annotation did not match HUGO gene symbols, ToppFun performed automatic re-annotation.…”
Section: Methodsmentioning
confidence: 99%
“…44 Recently, Erlich et al 45 demonstrated how gene prediction tools typically applied in combination with traditional mapping approaches, can also successfully be applied to prioritize candidate genes from exome resequencing experiments. They used three different bioinformatics tools (SUSPECTS, 46 ToppGene, 47 and Endeavour 15 ) to prioritize KIF1A as the most likely candidate gene for hereditary spastic paraparesis. Prioritization of the variants itself using MutationTaster, 48 Polyphen, 49 and SIFT 50 independently pointed to the variant in KIF1A as being the most likely pathogenic variant.…”
Section: Gene Identification Strategies For Exome Sequencing C Gilissmentioning
confidence: 99%
“…To select relevant genes among up and down regulated DE genes, perform enrichment analysis with ToppGenes and ToppCluster (Chen et al, 2009;Kaimal et al, 2010) for functional annotation enrichment pathways, biologic process and pathway with FDR p < 0.05.…”
Section: )mentioning
confidence: 99%